MOLECULAR AUTHENTICATION AND GENETIC DIVERSITY ANALYSIS OF HALOFEROX VOLCANII AND HALOBACTERIUM SALINARIUM FROM SALT BRINES - Sikkandar, Shahitha; Murugan, Kasi; Nair, Aneesh; Tilton, Florida (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective - Halophilic bacteria present in various high salt locations have shown to possess various commercially viable properties. An understanding of the microbial flora present in salt brines will help in the proper exploitation of this resource. Methods - In the current study, bacteria were isolated from salt brines and characterized. Followed by the morphological and biochemical characterization, the strains were subjected to molecular characterization. Genomic DNA was isolated and the 16s rRNA gene was amplified and sequenced. The sequence so obtained was subjected to sequence alignment analysis. The genetic diversity of the isolated strains were also analysed by RAPD PCR and phylogenetic relationship was established by dendrogram construction. Results – The isolated strains were found to be Haloferax volcanii and Halobacterium salinarium. The genetic diversity analyses of H. salinarium and H. volcanii reveal the resistance of the former to genetic variations. Conclusion - This study analysed the impact of environmental stress on the genotypes of H. salinarium and H. volcanii.